PERAN KEPEMIMPINAN DALAM MENTRANSFORMASIKAN TUJUAN INSTITUSIONAL DENGAN HASIL YANG TERUKUR: STUDI KASUS STAI AL-KIFAYAH RIAU - Akhyar, Yundri (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2026)
Many higher education institutions struggle to translate well-articulated institutional goals into concrete, measurable outcomes due to misalignment between leadership practices, organizational culture, and performance management systems. strategic plans remain normative rather than operational, limiting the institution’s ability to demonstrate accountable and sustainable performance improvement.This study aims to analyze the role of leadership in transforming institutional goals into measurable outcomes at STAI Al-Kifayah Riau. Using a qualitative approach with a case study method, the research explores how transformational and visionary leadership styles contribute to institutional performance within the context of Islamic higher education. Data were collected through in-depth interviews, participatory observation, and documentation, and analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that leadership at STAI Al-Kifayah Riau plays a vital role in aligning the institution’s vision and mission with its operational goals through three main dimensions: visionary leadership, participatory collaboration, and a culture of performance accountability grounded in Islamic values. This leadership approach not only enhances academic quality and managerial effectiveness but also fosters moral commitment and spiritual integrity among academic staff. The study implies that Islamic transformational leadership can serve as a strategic model for Islamic higher education institutions to achieve sustainable and accountable development while maintaining spiritual and ethical values in educational management.